2018
DOI: 10.1093/aob/mcy189
|View full text |Cite
|
Sign up to set email alerts
|

In situanalyses of inorganic nutrient distribution in sweetcorn and maize kernels using synchrotron-based X-ray fluorescence microscopy

Abstract: Background and Aims Understanding the spatial distribution of inorganic nutrients within edible parts of plant products helps biofortification efforts to identify and focus on specific uptake pathways and storage mechanisms. • Methods Kernels of sweetcorn (Zea mays) variety 'High zeaxanthin 103146' and maize inbred line 'Thai Floury 2' were harvested at two different maturity stages, and the distributions of K, P, S, Ca, Zn, Fe and Mn were examined in situ using synchrotron-based X-ray fluorescence microscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…(2019) analyzed immature (21 DAP) kernels from a single sweet corn ( sh2 ) variety via synchrotron-based X-ray fluorescence microscopy to reveal that potassium and calcium were generally present throughout the kernel, sulfur concentrated mainly in the axis of the embryo and the periphery of the endosperm, and the scutellum of the embryo had at least 20- fold higher concentrations of phosphorus, iron, zinc, and manganese than in the endosperm. Notably, Cheah et al . (2019) also showed that these spatial distribution maps for elements were highly similar to those of immature maize (non-sweet corn) kernels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) analyzed immature (21 DAP) kernels from a single sweet corn ( sh2 ) variety via synchrotron-based X-ray fluorescence microscopy to reveal that potassium and calcium were generally present throughout the kernel, sulfur concentrated mainly in the axis of the embryo and the periphery of the endosperm, and the scutellum of the embryo had at least 20- fold higher concentrations of phosphorus, iron, zinc, and manganese than in the endosperm. Notably, Cheah et al . (2019) also showed that these spatial distribution maps for elements were highly similar to those of immature maize (non-sweet corn) kernels.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Baxter et al . 2014; Cheah et al . 2019) could potentially lead to spurious associations with su1 and sh2 as shown for tocotrienols and certain carotenoids (Baseggio et al .…”
Section: Methodsmentioning
confidence: 99%
“…saccharata ), which has a sugary endosperm conferred by a single gene mutation ( Creech, 1965 ; Simonne et al , 1999 ), is a close relative of maize. The micronutrients of importance to human health, such as Zn, are found in high concentrations in the scutellum of sweetcorn and maize embryos ( Cheah et al , 2019b ). This micronutrient-rich embryo is typically removed during the processing of maize kernels by dry milling, whereas the entire kernel of sweetcorn is consumed.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the Zn-speciation of maize endosperm changed as the kernel matured, shifting from about 90% Zn-histidine at 21 DAP to about 83% Zn-phytate at 28 DAP, significantly reducing the bioavailability of the Zn in maize endosperm (Table 3.6). This increased complexation between Zn and phytate ligands could have possibly occurred in the aleurone layer (which was not separated from the endosperm tissue during analysis in this study), as P was also found to accumulate in the aleurone tissue in mature maize kernels (Chapter 3.1, (Cheah et al, 2019b)). This shift in endosperm Zn speciation is physiologically feasible, as it was reported that phytate-P concentration in maize kernels rapidly increase from 0.1 to 1.6 mg kg -1 DM between 15 and 30 DAP, which then continued to increase to 2.1 mg kg -1 at 40 DAP and 2.6 mg kg -1 at full maturity.…”
Section: Changes In Endosperm Zn Speciation As Maize Kernels Maturementioning
confidence: 87%
“…It was initially hypothesised that the advantage of using sweetcorn as a target crop for Zn biofortification was that the entire kernel is consumed, whereas in maize the embryo and the aleurone layers are removed during processing (Reddy and Love, 1999, Suri and Tanumihardjo, 2016, Gwirtz and Garcia-Casal, 2014. This is important as Zn accumulates at high concentration in the embryo and aleurone layer tissues (Chapter 3.1, (Cheah et al, 2019b)). However, this study revealed that the true benefit of obtaining Zn from a sweetcorn diet is the consumption of immature kernels, as compared with the consumption of mature kernels for maize.…”
Section: Benefits Of Zn Biofortification Of Sweetcorn and Maizementioning
confidence: 99%